Measuring Tourist Experience in Semarang City through an Advanced Recommendation System - Sutomo, Rudi; Kaisha Pratama, Daffa (Jurnal Komunikasi, Sains dan Teknologi, 2023)
In the tourism sector which includes recreation and holiday activities, the Indonesian tourism sector has a very important role because of its impact on the country's foreign exchange reserves. Indonesia, with its diverse attractions ranging from nature, culture, religion, family activities, shopping and gastronomy, presents many choices for tourists. The city of Semarang is actively increasing its tourism offerings, but the sheer number of choices can overwhelm tourists. This research presents an advanced recommendation system based on collaborative filtering and content-based filtering techniques. By leveraging historical travel data, including attraction visits, ratings, and frequently visited categories, the system provides tailored suggestions. Content-based filtering prioritizes tourist attractions such as Chinatown Semarang, Kampoeng Djadhoel Semarang, Kapal Mosque Semarang, Tugu Muda Semarang, and Tinjomoyo Forest Tourism Semarang based on ratings. Collaborative filtering resulted in recommendations such as Gua Maria Kerep Ambarawa (rating: 4.8), La Kana Chapel (rating: 4.5), Palagan Ambarawa Monument (rating: 4.4), Eling Bening Tourism (rating: 4.3), and Kampoeng Kopi Banaran (rating: 4.3).In a world where choices are many and time is limited, this advanced recommendation system simplifies travel decisions, elevating ordinary trips into extraordinary adventures. This heralds the future of tourism, where technology aligns with exploration to uncover Semarang's hidden treasures.” of 4.3.